Simulated microgravity affects directional growth of pollen tubes in candidate space crops - Iovane, Maurizio; Izzo, Luigi Gennaro; Romano, Leone Ermes; Aronne, Giovanna (Frontiers in Plant Science, 2023)
Background: Long-term space missions will necessarily require producing viable seeds to be used for plant cultivation over time under altered gravity conditions. Pollen is known to play a key role in determining seed and fruit production over seed-to-seed cycles, but very few studies have evaluated pollen functionality in altered gravity. Methods: We performed ground-based experiments to test how simulated microgravity can affect directional growth of pollen tubes as potential bottleneck in seed and fruit set.The effect of clinorotation was assessed in pollen of Solanum lycopersicum L. cv. ‘Micro-Tom’ and Brassica rapa L. var. silvestris, both eligible for cultivation in space. Pollen tube length and tortuosity were compared under 1g and simulated microgravity with a uniaxial clinostat. Results: The main results highlighted that simulated microgravity significantly increased pollen tube length and tortuosity compared to 1g conditions. Further, clinorotation prompted a differential effect on pollen germination between S. lycopersicum and B. rapa. A more in-depth analysis evaluating the effect of gravity on directional growth of pollen tubes excluded gravitropic responses as responsible for tube tip position reached after germination. Discussion: This research provides new insights into how altered gravity can interfere with plant reproduction and in particular with microgametophyte functionality. Our findings represent a basis for further studies aimed at understanding the effect of real microgravity on plant reproduction and at developing countermeasures to ensure seed-to-seed cultivation in long term space missions and achieve self-sufficiency in food supplies from Earth.